A novel real time PCR assay using melt curve analysis for ivory identification. (October 2016) - Kitpipit, Thitika; Penchart, Kitichaya; Ouithavon, Kanita; Satasook, Chutamas; Linacre, Adrian; Thanakiatkrai, Phuvadol
Highlights: ⿢ The real-time PCR based assay was proposed for ivory species identification. ⿢ Three extant elephant species were clearly classified by the developed assay. ⿢ The assay was fully validated according to ISFG recommendation. ⿢ The assay can be used in conjunction with the direct PCR method. Abstract: Demand for ivory and expansion of human settlements have resulted in a rapid decline in the number of elephants. Enforcement of local and international laws and regulations requires identification of the species from which any ivory, or ivory products, originated. Further geographical assignment of the dead elephant from which the ivory was taken can assist in forensic investigations. In this study, a real-time PCR assay using melt curve analysis was developed and fully validated for forensic use. The presence or absence of three Elephantidae-specific and elephant species-specific melting peaks was used to identify the elephant species. Using 141 blood and ivory samples from the three extant elephant species, the assay demonstrated very high reproducibility and accuracy. The limit of detection was as low as 0.031 ng of input DNA for conventional amplification and 0.002 ng for nested amplification. Both DNA concentrations are typically encountered in forensic casework, especially for degraded samples. No cross-reactivity was observed for non-target species. Evaluation of direct amplification and nested amplification demonstrated the assay's flexibility and capability of analyzing low-template DNA samples and aged samples. Additionally, blind trial testing showed the assay's suitability application in real casework. In conclusion, wildlife forensic laboratories could use this novel, quick, and low-cost assay to help combat the continuing poaching crises leading to the collapse of elephant numbers in the wild.